What can the common fruit fly teach us about stroke?: lessons learned from the hypoxic tolerant Drosophila melanogaster - Quadros-Mennella, Princy S.; Lucin, Kurt M.; White, Robin E. (Frontiers in Cellular Neuroscience, 2024)
Stroke, resulting in hypoxia and glucose deprivation, is a leading cause of death and disability worldwide. Presently, there are no treatments that reduce neuronal damage and preserve function aside from tissue plasminogen activator administration and rehabilitation therapy. Interestingly, Drosophila melanogaster, the common fruit fly, demonstrates robust hypoxic tolerance, characterized by minimal effects on survival and motor function following systemic hypoxia. Due to its organized brain, conserved neurotransmitter systems, and genetic similarity to humans and other mammals, uncovering the mechanisms of Drosophila's tolerance could be a promising approach for the development of new therapeutics. Interestingly, a key facet of hypoxic tolerance in Drosophila is organism-wide metabolic suppression, a response involving multiple genes and pathways. Specifically, studies have demonstrated that pathways associated with oxidative stress, insulin, hypoxia-inducible factors, NFκB, WNT, Hippo, and Notch, all potentially contribute to Drosophila hypoxic tolerance. While manipulating the oxidative stress response and insulin signaling pathway has similar outcomes in Drosophila hypoxia and the mammalian middle cerebral artery occlusion (MCAO) model of ischemia, effects of Notch pathway manipulation differ between Drosophila and mammals. Additional research is warranted to further explore how other pathways implicated in hypoxic tolerance in Drosophila, such as NFκB, and Hippo, may be utilized to benefit mammalian response to ischemia. Together, these studies demonstrate that exploration of the hypoxic response in Drosophila may lead to new avenues of research for stroke treatment in humans.